Fungicide Difenoconazole Induced Biochemical and Developmental Toxicity in Wheat (Triticum aestivum L.) - Runqiang Liu (MDPI AG, 2021)
Difenoconazole is one of the most commonly used fungicides to prevent and treat plant diseases caused by certain fungi. Due to increasing usage, more difenoconazole has been released into the environment and caused environment pollution. However, the potential impact of difenoconazole on plant growth and development and its involved mechanism are unclear. In this study, we discovered that difenoconazole exposure significantly inhibited plant growth, evidenced by the decrease in root dry weight, total root length, and surface area by 20–70%, 43–73%, and 26–66%, respectively, under different regimes of treatment concentrations and periods. Difenoconazole exposure also significantly inhibited shoot growth and development by decreasing 33–61% of the shoot dry weight and 50–65% of the leaf area. Difenoconazole exposure induced plant leaf cells to generate more ROS (O2•− and H2O2) and MDA, which resulted in a decreased chlorophyll content and then inhibited leaf photosynthesis. Difenoconazole exposure also induced the activities of superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (G-POD), and ascorbate peroxidase (APX) in the roots and leaves of the wheat seedlings. SOD and APX activities were higher and more stable in the roots than those in the leaves. Based on our study, plant roots exhibited a more pronounced superoxide radical scavenging ability than plant leaves. In summary, difenoconazole exposure caused oxidative stress, reduced chlorophyll biosynthesis and functions, and then inhibited wheat plant growth and development.